2010
DOI: 10.1121/1.3290744
|View full text |Cite
|
Sign up to set email alerts
|

The neural code for interaural time difference in human auditory cortex

Abstract: A magnetoencephalography study was conducted to reveal the neural code of interaural time difference (ITD) in the human cortex. Widely used crosscorrelator models predict that the code consists of narrow receptive fields distributed to all ITDs. The present findings are, however, more in line with a neural code formed by two opponent neural populations: one tuned to the left and the other to the right hemifield. The results are consistent with models of ITD extraction in the auditory brainstem of small mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 15 publications
10
45
0
Order By: Relevance
“…It is also consistent with human fMRI data, which has shown that primary auditory cortex is highly sensitive to both ear of stimulation (Woods et al 2010;Stecker et al 2015;Gutschalk and Steinmann 2015) and interaural level differences (ILDs) Stecker et al 2015), but not ITD (von Kriegstein et al 2008;McLaughlin et al 2015). Although ITD sensitivity has been found in human auditory cortex, it is generally located in more posterolateral areas (von Kriegstein et al 2008;McLaughlin et al 2015) and in long-as opposed to middle-latency components of the AER (McEvoy et al 1993;Salminen et al 2009;Salminen et al 2010;Magezi and Krumbholz 2010;Gutschalk et al 2012) (for reviews, see Salminen et al 2012;Gutschalk 2014). In any case, the population-level representation of ITD at the level of the midbrain might be fundamentally different from that found in primary AC (Thompson et al 2006;von Kriegstein et al 2008;Belliveau et al 2014;Vonderschen and Wagner 2014;Yao et al 2015), though this is in need of further clarification.…”
Section: Spatial Representation In the Auditory Pathwaysupporting
confidence: 74%
“…It is also consistent with human fMRI data, which has shown that primary auditory cortex is highly sensitive to both ear of stimulation (Woods et al 2010;Stecker et al 2015;Gutschalk and Steinmann 2015) and interaural level differences (ILDs) Stecker et al 2015), but not ITD (von Kriegstein et al 2008;McLaughlin et al 2015). Although ITD sensitivity has been found in human auditory cortex, it is generally located in more posterolateral areas (von Kriegstein et al 2008;McLaughlin et al 2015) and in long-as opposed to middle-latency components of the AER (McEvoy et al 1993;Salminen et al 2009;Salminen et al 2010;Magezi and Krumbholz 2010;Gutschalk et al 2012) (for reviews, see Salminen et al 2012;Gutschalk 2014). In any case, the population-level representation of ITD at the level of the midbrain might be fundamentally different from that found in primary AC (Thompson et al 2006;von Kriegstein et al 2008;Belliveau et al 2014;Vonderschen and Wagner 2014;Yao et al 2015), though this is in need of further clarification.…”
Section: Spatial Representation In the Auditory Pathwaysupporting
confidence: 74%
“…Previous neuroimaging studies have measured the change in neural activity elicited by a change in sound source location following a brief adapting stimulus in order to compare two-channel and topographic models of sound localisation and have demonstrated that predictions generated from a two-channel model best match the observed data (Salminen et al, 2009;Salminen et al, 2010;Magezi and Krumbholz, 2010;Briley et al, 2013). In order to compare our observed behavioural performance to that predicted by FIG.…”
Section: Modelsmentioning
confidence: 88%
“…Three simple models were developed where auditory space was represented as a two-channel model, a topographic model, or a modified topographic model, based on recent nonbehavioural imaging studies that tested brain responses to shifts in sound source locations (Salminen et al, 2009;Salminen et al, 2010;Magezi and Krumbholz, 2010), and predictions were generated for psychophysical performance in this task. Specifically, the two-channel and modified topographic model predicted that performance should be better around the midline than in the periphery, while only the modified topographic model, predicted that performance should differ (specifically should be superior) for inward-as compared to outward-moving sounds.…”
Section: Degrees Of Freedommentioning
confidence: 99%
See 1 more Smart Citation
“…Using selective adaptation paradigms, they provided evidence that intracranial azimuth judgments are based on the relative outputs of three neural-perceptual channels with broad tuning to the left and right acoustic hemifields, and to the midline. The existence of left and right hemifield channels has also received support from human neuroimaging studies (Magezi and Krumbholz, 2010;Salminen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%